PROJECTIONS OF HYPERSURFACES IN R-4 WITH BOUNDARY TO PLANES - Martins, Luciana F. [UNESP]; Nabarro, Ana Claudia (Cambridge University Press, 2014)
We study orthogonal projections of generic embedded hypersurfaces in (4) with boundary to 2-spaces. Therefore, we classify simple map germs from (3) to the plane of codimension less than or equal to 4 with the source containing a distinguished plane which is preserved by coordinate changes. We also go into some detail on their geometrical properties in order to recognize the cases of codimension less than or equal to 1.